Life Cycle Assessment of honey: Considering the pollination service - Ioannis Arzoumanidis; Andrea Raggi; Luigia Petti (Administrative Sciences, 2019)
Life Cycle Assessment (LCA) has been increasingly used for the improvement of the environmental performance of products and services, including food systems. Amongst them, however, honey appears to have been rarely analysed. Furthermore, the pollination by honeybees can be regarded as one of the functions of an apiculture system and is of utmost importance both for natural ecosystems and agriculture. When implementing an LCA of an apiculture system, the pollination service can and should be considered as one of the functions of a multifunctional system and the issue of how to deal with this multifunctionality in the modelling of that system should be considered carefully. The aim of this paper is to explore the economic value of pollination as a potential basis for managing multifunctionality in LCA modelling as well as its implementation in a case study. Economic allocation was performed between the pollination service and honey production. The results demonstrated that the production phase is the most impactful one for most of the environmental categories (due to the use of glass for the honey jars and electricity consumption during the storage of supers in refrigerator rooms), followed by the distribution phase. Finally, the most affected environmental impact category appeared to be natural land transformation, followed by marine ecotoxicity, freshwater eutrophication and human toxicity.
Keywords: 350; LCA; honey; pollination; multifunctionality; economic value of honey